Modelling of a novel cost saving automated stand fan - Mohd Yusof, Zulkhairi; Masum Billah, Md; Kadir, Kushsairy; Mahal Binti Hashim, Taj; Nasir, Haidawati (International Journal of Engineering and Technology, 2019)
In tropical forest countries like Malaysia where the normally temperature is 27â„ƒ in most region it becomes very uncomfortable to live with-out a fan. Electric fan become electrical appliance that have been used widely in our daily life. By pressing switch button, we can operate ceiling fan or stand fan manually. In this research, we will develop a sensory system for detection of the presence of human and the position of human in a room. The sensory system will be embedded with stand fan. It will facilitate by automatically turn on/off the fan depends on the presence of human. Fan speed will also be controlled automatically depends on the environment temperature. Furthermore, it will also allow the fan to oscillate in a certain range depends on the motion or presence of numbers of human. The proposed automated fan will save approximate 50% operating cost by operating automatically only the presence of the subjects.Â Â